Research on efficient impurity removal via chlorination roasting-acid leaching of low-grade molybdenum concentrate - Dehao Dou; Huan Tian; Tu Hu; Baocheng Zhou; Guo Lin; Libo Zhang; Jianwei Song; Junkui Shi; Yanfen Yang (Minerals Engineering, 2026)

Dust transport and impacts on secondary aerosol formation: Contrasting strong dust and floating dust events - Yanfen Lin; Qingyan Fu; Ziwei Liu; Zhijian Ding; Fan Yang; Ali Darvishi Boloorani; Cheng Huang; Juntao Huo; Qian Wang; Jia Chen; Qiongzhen Wang; Sabur F. Abdullaev; et al. (Atmospheric Environment, 2026)

Decoration of the ferritin nanocage surface to regulate the interfacial structure of emulsions for the development of a chitosan-based active film applied to Agaricus bisporus preservation - Kai Lin; Wenjie Zhao; Pengya Du; Suchen Zhao; Cailin Song; Yuanhao Guo; Jinling Cao; Yanfen Cheng; Feier Cheng; Wenfei Zhao; Cuiping Feng; Shaojun Yun (Food Hydrocolloids, 2026)

A comprehensive review on the mechanism, applicability and selection of chlorinating agents - Dehao Dou; Huan Tian; Tu Hu; Baocheng Zhou; Guo Lin; Libo Zhang; Jianwei Song; Junkui Shi; Yanfen Yang (Journal of Environmental Chemical Engineering, 2026)

Aerococcus christensenii: an emerging pathogen associated with infections and bacteremia in pregnancy—genomic insights and pathogenicity evaluation - Yugui Lin; Jialin He; Qiaoliang Zhang; Yanfen Li; Jialong Ke; Chunxiu Lin; Bingyan Yao; Chilun Zhang; Nan Tan (Functional & Integrative Genomics, 2025)

Low-carbon investment volatility under policy uncertainty: Evidence from equity markets and implications for carbon capture deployment - Dapeng Lin; Yanfen Wang; Chang Wang; Wen Jiang; Liyuan Zhang; Shuo Hu; Kai Du; Chengdong Yuan (Journal of Cleaner Production, 2025)

Organic nitrates in coastal aerosols: Seasonal dynamics, influencing factors, and formation pathways - Mengke Tian; Zhijian Ding; Jia Chen; Juntao Huo; Guochen Wang; Jian Xu; Hao Li; Ziwei Liu; Yunkai Wang; Nan Ye; Xiaofei Qin; Yanfen Lin; et al. (Atmospheric Environment, 2025)

Water availability and hydrological connectivity mediate the responses of alpine soil prokaryotes to temperature changes at the watershed scale - Wencong Lv; Liyuan Ma; Jianqing Du; Li Tang; Biao Zhang; Danhong Chen; Qiang Liu; Shutong Zhou; Zhe Pang; Lin Chen; Yanbin Hao; Kai Xue; et al. (Journal of Environmental Management, 2025)

Synergistic effect of dextran and ergosterol: A venue for fabricating a water-in-oil pickering emulsion gel as a solid fat substitute in cream cheese - Kai Lin; Pengya Du; Pengfei Dong; Yaxin Wang; Yuanhao Guo; Jinling Cao; Yanfen Cheng; Feier Cheng; Wenfei Zhao; Cuiping Feng; Shaojun Yun (Food Hydrocolloids, 2025)

Nitrogen level determines arbuscular mycorrhizal fungi nitrogen uptake rate of Stipa purpurea in alpine steppe - Jiahui Sun; Yu Tang; Keyu Chen; Shijie Ren; Hailan Shi; Qiang Dong; Junfu Dong; Lin Zhang; Xiaoyong Cui; Yanfen Wang; Baoming Ji; Jing Zhang (Plant and Soil, 2025)

Rational design of high-entropy P2/O3 biphasic layered cathodes for enhanced sodium storage performance - Yanfen Wen; Chungang Lin; Hao Shen; Kai Fang; Fupeng Li; Chengkui Luo; Xiaolin Wang; Huilin Peng; Yu Qiao; Shuxin Zhuang; Mi Lu (Chemical Engineering Journal, 2025)

Evaluating long-term reductions in trace metal emissions from shipping in Shanghai - Meng Wang; Yusen Duan; Juntao Huo; Jia Chen; Yanfen Lin; Qingyan Fu; Tao Wang; Yu Huang; Junji Cao; Shun-cheng Lee (Journal of Hazardous Materials, 2024)

Unraveling the mechanism of CTAB-assisted in situ synthesis of CuAlO -doped 0D CeO2 heterostructures for boosting simultaneous removal of NO, benzene, and toluene: The role of different active sites - Yin Chen; Yanfen Liao; Zhuofan Chen; Lin Chen; Xiaoqian Ma (Chemical Engineering Journal, 2024)

Immunotherapy shapes B-cell receptor repertoire to induce anti-tumor antibodies production in colon and lung cancer - Hang Su; Yimeng Wang; Sajid Khan; Yinan Huang; Zhenfei Yi; Na Zhu; Zhenghao Li; Feng Leng; Yanfen Chen; Lin Yang; Takaji Matsutani; Zhenghong Lin; et al. (Genome Instability & Disease, 2024)

Glycosylation of a ferritin nanocage with dextran as a novel emulsifier for the construction of dual-compartmental pickering emulsions to co-encapsulate hydrophobic bioactive compounds - Guo Yuanhao; Wang Yaxin; Dong Pengfei; Wang Shengnan; Lin Kai; Hou Jiangyan; Cui Fangming; Bi Shuyu; Cao Jinling; Cheng Yanfen; Cheng Feier; Yun Shaojun; et al. (Journal of Food Engineering, 2024)

Water-in-oil Pickering emulsion using ergosterol as an emulsifier solely - Yaxin Wang; Yuanhao Guo; Pengfei Dong; Kai Lin; Pengya Du; Jinling Cao; Yanfen Cheng; Feier Cheng; Shaojun Yun; Cuiping Feng (Food Research International, 2024)

Concurrent Assessment on Blood Lead in Young Children and Toy Lead in Shanghai - Jiayu Peng; Zhenyan Gao; Jian Xu; Yanfen Lin; Aaron J. Specht; Shuwen Chen; Linda H. Nie; Linhua Huang; Chonghuai Yan (Exposure and Health, 2024)

Unraveling the multi-pollutant removal using M-MoWTi (M = Fe, Mn, Cr) catalyst: experiment and mechanistic study of competition for active sites - Zhuofan Chen; Lin Chen; Yanfen Liao; Yin Chen; Xiaoqian Ma (Environmental Science and Pollution Research, 2024)

A novel index for assessing the rural population hollowing at fine spatial resolutions based on Tencent social media big data: A case study in Guangdong Province, China - Fang Wang; Shaoying Li; Lin Liu; Feng Gao; Yanfen Feng; Zilong Chen (Land Use Policy, 2024)

Evolution and trends of new energy vehicle policy research hotspots: an analysis based on a Citespace knowledge graph - Lei Zhang; Yanfen Lin; Siyu Zhou; Quande Qin (Environmental Science and Pollution Research, 2024)

P2/O3 biphase integration promoting the enhancement of structural stability for sodium layered oxide cathode - Chungang Lin; Peng Dai; Xiaolin Wang; Jingjing Sun; Shuxin Zhuang; Lina Wu; Mi Lu; Yanfen Wen (Chemical Engineering Journal, 2024)

Relationships between nitrogen-specific genes and soil potentials are more complex than single linear ones - Yanfen Wang; Shutong Zhou; Biao Zhang; Jianqing Du; Anquan Xia; Lin Chen; Li Tang; Kui Wang; Wenjing Liu; Zongsong Wang; Lizhen Cui; Kai Xue (Applied Soil Ecology, 2023)

Integrating ICESat-2 laser altimeter observations and hydrological modeling for enhanced prediction of climate-driven lake level change - Cong Liu; Ronghai Hu; Yanfen Wang; Hengli Lin; Dongli Wu; Yi Dai; Yongchao Zhu; Zhigang Liu; Dasheng Yang; Quanjun Zhang; Changliang Shao; Zhengyi Hu (Journal of Hydrology, 2023)

Relationship between light absorption properties of black carbon and aerosol origin at a background coastal site - Haiyan Li; Chengfeng Liu; Hao Li; Guochen Wang; Xiaofei Qin; Jia Chen; Yanfen Lin; Juntao Huo; Qingyan Fu; Yusen Duan; Congrui Deng; Kan Huang (Science of The Total Environment, 2023)

Investigation on co-disposal technology of sludge and municipal solid waste based on numerical simulation - Tao Lin; Yanfen Liao; Tonghua Dai; Xiaoqian Ma (Fuel, 2023)

Airborne black carbon variations during the COVID-19 lockdown in the Yangtze River Delta megacities suggest actions to curb global warming - Hao Li; Kan Huang; Qingyan Fu; Yanfen Lin; Jia Chen; Congrui Deng; Xudong Tian; Qian Tang; Qingchuan Song; Zhen Wei (Environmental Chemistry Letters, 2022)

Anaerobic methane oxidation linked to Fe(III) reduction in a Candidatus Methanoperedens ‐ enriched consortium from the cold Zoige wetland at Tibetan Plateau - Lin Chen; Lingyan Li; Shengjie Zhang; Wenting Zhang; Kai Xue; Yanfen Wang; Xiuzhu Dong (Environmental Microbiology, 2022)
Summary Anaerobic oxidation of methane (AOM) is a microbial process degrading ample methane in anoxic environments, and Ca. Methanoperedens mediated nitrate‐ or metal‐reduction linked AOM is believed important in freshwater systems. This work, via 16S rRNA gene diversity survey and 16S rRNA quantification, found abundant Ca. Methanoperedens along with iron in the cold Zoige wetland at Tibetan Plateau. The wetland soil microcosm performed Fe(III) reduction, rather than nitrate‐ nor sulphate‐reduction, coupled methane oxidation (3.87 μmol d −1 ) with 32.33 μmol Fe(II) accumulation per day at 18°C, but not at 30°C. A metagenome‐assembled genome (MAG) recovered from the microcosm exhibits ~74% average nucleotide identity with the reported Ca. Methanoperedens spp. that perform Fe(III) reduction linked AOM, thus a novel species Ca. Methanoperedens psychrophilus was proposed. Ca. M. psychrophilus contains the whole suite of CO 2 reductive methanogenic genes presumably involving in AOM via a reverse direction, and comparative genome analysis revealed its unique gene categories: the multi‐heme clusters (MHCs) cytochromes, the S‐layer proteins highly homologous to those recovered from lower temperature environments and type IV pili, those could confer Ca. M. psychrophilus of cold adaptability. Therefore, this work reports the first methanotroph implementing AOM in an alpine wetland.

Ambient climate determines the directional trend of community stability under warming and grazing - Peipei Liu; Wangwang Lv; Jianping Sun; Caiyun Luo; Zhenhua Zhang; Xiaoxue Zhu; Xingwu Lin; Jichuang Duan; Guangping Xu; Xiaofeng Chang; Yigang Hu; Qiaoyan Lin; et al. (Global Change Biology, 2021)
Changes in ecological processes over time in ambient treatments are often larger than the responses to manipulative treatments in climate change experiments. However, the impacts of human‐driven environmental changes on the stability of natural grasslands have been typically assessed by comparing differences between manipulative plots and reference plots. Little is known about whether or how ambient climate regulates the effects of manipulative treatments and their underlying mechanisms. We collected two datasets, one a 36‐year long‐term observational dataset from 1983 to 2018, and the other a 10‐year manipulative asymmetric warming and grazing experiment using infrared heaters with moderate grazing from 2006 to 2015 in an alpine meadow on the Tibetan Plateau. The 36‐year observational dataset shows that there was a nonlinear response of community stability to ambient temperature with a positive relationship between them due to an increase in ambient temperature in the first 25 years and then a decrease in ambient temperature thereafter. Warming and grazing decreased community stability with experiment duration through an increase in legume cover and a decrease in species asynchrony, which was due to the decreasing background temperature through time during the 10‐year experiment period. Moreover, the temperature sensitivity of community stability was higher under the ambient treatment than under the manipulative treatments. Therefore, our results suggested that ambient climate may control the directional trend of community stability while manipulative treatments may determine the temperature sensitivity of the response of community stability to climate relative to the ambient treatment. Our study emphasizes the importance of the context dependency of the response of community stability to human‐driven environmental changes.

Phylogenetic analysis of infectious bronchitis virus circulating in southern China in 2016–2017 and evaluation of an attenuated strain as a vaccine candidate - Libin Chen; Bin Xiang; Yanfen Hong; Qian Li; Haoyun Du; Qiuyan Lin; Ming Liao; Tao Ren; Chenggang Xu (Archives of Virology, 2021)

Impact of mixed anthropogenic and natural emissions on air quality and eco-environment—the major water-soluble components in aerosols from northwest to offshore isle - Yilun Jiang; Guoshun Zhuang; Qiongzhen Wang; Kan Huang; Congrui Deng; Guangyuan Yu; Chang Xu; Qingyan Fu; Yanfen Lin; Joshua S. Fu; Mei Li; Zhen Zhou (Air Quality, Atmosphere & Health, 2018)

Effects of rainfall amount and frequency on vegetation growth in a Tibetan alpine meadow - Baocheng Zhang; Junji Cao; Yanfen Bai; Xuhui Zhou; Zhigang Ning; Songjie Yang; Lin Hu (Climatic Change, 2013)

Warming and grazing affect soil labile carbon and nitrogen pools differently in an alpine meadow of the Qinghai–Tibet Plateau in China - Yichao Rui; Shiping Wang; Zhihong Xu; Yanfen Wang; Chengrong Chen; Xiaoqi Zhou; Xiaoming Kang; Shunbao Lu; Yigang Hu; Qiaoyan Lin; Caiyun Luo (Journal of Soils and Sediments, 2011)

The sources and seasonal variations of organic compounds in PM2.5 in Beijing and Shanghai - Yilun Jiang; Ximei Hou; Guoshun Zhuang; Juan Li; Qiongzhen Wang; Rong Zhang; Yanfen Lin (Journal of Atmospheric Chemistry, 2009)

Emission of fine organic aerosol from traditional charcoal broiling in China - Ximei Hou; Guoshun Zhuang; Yanfen Lin; Juan Li; Yilun Jiang; Joshua S. Fu (Journal of Atmospheric Chemistry, 2008)

The chemistry of heavy haze over Urumqi, Central Asia - Juan Li; Guoshun Zhuang; Kan Huang; Yanfen Lin; Qiongzhen Wang; Yuhong Guo; Jinghua Guo; Shulong Yu; Caixia Cui; Joshua S. Fu (Journal of Atmospheric Chemistry, 2008)